1997
DOI: 10.1021/ie960250h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Glucose Epimerization and Decomposition in Subcritical and Supercritical Water

Abstract: Glucose decomposition kinetics in subcritical and supercritical water were studied for the temperatures 573, 623, and 673 K, pressures between 25 and 40 MPa, and residence times between 0.02 and 2 s. Glucose decomposition products were fructose, saccharinic acids, erythrose, glyceraldehyde, 1,6-anhydroglucose, dihydroxyacetone, pyruvaldehyde, and small amounts of 5-hydroxymethylfurfural. Fructose was also studied and found to decompose to products similar to those of glucose, except that its epimerization to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
230
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(249 citation statements)
references
References 11 publications
15
230
1
3
Order By: Relevance
“…Glucose as an aldohexose may be involved in competing reaction pathways leading to nonfuran cyclic ethers by-products formation. The C-C bond scissions may also occur in this case [Kabyemela et al, 1997;Jing & Lu, 2008]. On the other hand some enhancement of HMF yields obtained from sucrose as a carbohydrate source was observed.…”
Section: Stanisław Kowalski 1 * Marcin Lukasiewicz 1 Aleksandra Dumentioning
confidence: 94%
“…Glucose as an aldohexose may be involved in competing reaction pathways leading to nonfuran cyclic ethers by-products formation. The C-C bond scissions may also occur in this case [Kabyemela et al, 1997;Jing & Lu, 2008]. On the other hand some enhancement of HMF yields obtained from sucrose as a carbohydrate source was observed.…”
Section: Stanisław Kowalski 1 * Marcin Lukasiewicz 1 Aleksandra Dumentioning
confidence: 94%
“…62,63 Despite the difficulty of developing an industrial process based on these high temperatures and short residence times, the company Renmatix® has developed extensive intellectual property in this area and describes its Plantrose™ process as relying on a two-stage process similar in concept to the one ). Kinetic data was taken from Schwald and Bobleter, 199 Adschiri et al 200 Mochidzuki et al 201 Sasaki et al 61 Bobleter and Pape, 202 Amin and Reid, 203 Kabyemela et al 204 and Matsumura et al 205 (B) Predicted glucose production from cellulose in pure water. Insert is a close-up for short reaction times.…”
Section: Degradation Products ð4þmentioning
confidence: 99%
“…8) Many researchers have investigated the isomerization of saccharides such as glucose, mannose, and fructose in 100% (v/v) subcritical water. [9][10][11] It was reported that aldoses isomerized easily than ketoses in 100% (v/v) subcritical water. 10) Although kinetic analysis revealed that mannose was isomerized most easily to fructose among glucose, mannose, and fructose, the yields of fructose and glucose from mannose were still low.…”
mentioning
confidence: 99%